Coagulation-flocculation as pretreatment for rubber glove wastewater reclamation system: article - Mohd Zaini, Siti Nur Umira; Lim, Ying Pei (2019)
In this work, the rubber glove effluent was treated by using coagulation-flocculation method. Two different types of coagulant, i.e polyaluminium chloride (PAC) and ferric chloride (FC) were used in jar test. The wastewater was initially characterized in terms of pH, ammonical nitrogen (AN), chemical oxygen demand (COD), nitrate, total suspended solids (TSS), turbidity, total dissolved solids (TDS) and trace elements by using standard method. In jar test, COD and turbidity removal efficiency was used as performance indicator for the coagulation-flocculation process. Three parameters were carried out in jar test i.e pH (6-10), coagulants dosages (100- 500 mg/L) and flocculants dosages (1-5 mg/L). The optimum coagulation-flocculation conditions for FC were pH 9, 400 mg/L coagulant dosage and 1 mg/L flocculants dosage with COD removal efficiency within 63% to 88%. As for PAC, the optimum conditions achieved at pH 7.5, 400 mg/L coagulant dosage and 5 mg/L flocculants dosage with COD removal efficiency 38% to 98%. Overall, PAC shows greater turbidity removal efficiency up to 98% as compared to FC (94%). In conclusion, coagulant-flocculants could be used as an effective ways to reduce the turbidity and chemical oxygen demand (COD) level for rubber glove effluent.